2009
DOI: 10.1007/s11144-009-0063-8
|View full text |Cite
|
Sign up to set email alerts
|

Partial oxidation of methane into syngas on Pt-supported mixed oxides: effect of surface/lattice oxygen mobility in complex oxides on the kinetic features of the reaction and performance stability

Abstract: INGENIERIE+ABB:CMI:EGUNon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…It increases the concentration of oxygen vacancies and the surface oxygen mobility and, as a result, increases the rate of transformation of adsorbed CH x species into CO and H 2 at the Pt-support interface. As for the same catalysts in POM, the apparent first-order rate constants of the methane transformation in DR were estimated for all three catalysts using the model of a plug-flow reactor [5,6]. Comparison of these values revealed that the constants of DR are several times lower than those of POM (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It increases the concentration of oxygen vacancies and the surface oxygen mobility and, as a result, increases the rate of transformation of adsorbed CH x species into CO and H 2 at the Pt-support interface. As for the same catalysts in POM, the apparent first-order rate constants of the methane transformation in DR were estimated for all three catalysts using the model of a plug-flow reactor [5,6]. Comparison of these values revealed that the constants of DR are several times lower than those of POM (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The basic characteristics of active components, procedures of their supporting on separate corundum channels and experimental features were described in detail earlier [5][6][7]. The catalytic activity in DR was measured at atmospheric pressure in the temperature range from 600 to 850°C, and at contact times in the range from 4.7 to 15.0 ms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations